Highland cattle and Radix labiata, the hosts of Fascioloides magna - Leontovyč, Roman; Košťáková, Monika; Siegelová, Veronika; Melounová, Klára; Pankrác, Jan; Vrbová, Kristýna; Horák, Petr; Kašný, Martin (BMC veterinary research, 2014)
BACKGROUND: Fascioloides magna is a pathogenic fluke introduced to Europe ca 140 years ago. As it is spreading over the continent, new intermediate and definitive hosts might be involved in transmission of the parasite. In Europe, several studies reported potential new intermediate snail hosts (Radix spp.) for F. magna, and also several cases of fascioloidosis of wild and domestic animals were published. However, the data based on molecular and histological analyses confirming these findings remained unreported. This study aims to refer to unique findings of F. magna in European snails and domestic animals (the first observation in the Czech Republic in the last 30 years) and demonstrate the use of molecular techniques in determination of F. magna. RESULTS: Two snails of R. labiata naturally infected with F. magna were found; mature cercariae and daughter rediae were observed. Maturity of cercariae was checked by histological methods, however, their ability to encyst was not confirmed. Co-infection of F. magna and Fasciola hepatica in the liver of two highland cattle bulls was proved. Adult fasciolid flukes producing eggs were found in the liver pseudocysts (F. magna) and the bile ducts (F. hepatica). Identification of intermediate hosts, intramolluscan stages, adult flukes and eggs was performed by sequencing the ITS2 region. Connection of F. magna pseudocysts with the gut (via the bile ducts) was not confirmed by means of histological and coprological examinations. CONCLUSIONS: For the first time, Radix labiata was confirmed as the snail host for F. magna under natural conditions and, together with the finding of F. magna infection in cattle, we can expect further transmission of F. magna from wildlife to livestock in localities shared by these hosts.
Keywords: skot; Česká republika; Fasciolidae; Cattle; Snails; Czech Republic; infekce červy třídy Trematoda; nemoci skotu; Male; Animals; Trematode Infections; mužské pohlaví; hlemýždi; zdroje nemoci; Cattle Diseases; zvířata; Disease Reservoirs